القصيدة التشكيلية - غنيم, غسان; سعيد, مبارك (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى توضيح موضوع القصيدة التشكيلية ، فإذا كان الشعر ديوان العرب ، فكم لهذا الديوان من قيمة فنية ومعنوية سجلت بوح الشعراء ، وأرّخت لمعاركهم الحياتية والجهادية وأظهرت جوى قلوبهم في إطار كان للرقابة الشكلية فيه نصيب فإذا أمعنا النظر في القصيدة الشعرية والتشكيلية منها بخاصة رأينا أنها تمثل نقلة تطبيقية لفكر جمالي معبّر عن عصره ، فبعد أن كان العرب يعتمدون على وحدة البيت أصبحت القصيدة التشكيلية ذات سمات تعبيرية تكتنفها نظرة جمالية كلية ، بكل أبعادها التعبيرية واللفظية والتشكيلية . This research aims to explain the subject of the formal verse. As far as verse was Arab's volume, how much value does it have artistically and spiritually showed poets’ will and chronically demonstrated how their life and struggle was. It also showed their deepest feelings in a frame of shape formalities censorship. If we have a close look at a piece of verse,especially, a formal one, we will find that it symbolizes a practical shift for an aesthetic thought that was expressed in the era when Arabs depended on one -complete- line poem and it became the formal poem that conveyed expressionism features of a total aesthetic point of view. Thus, it overcame the partiality of one – complete – poem line to reach the totality of poems unity as an artistic experiment with all its expressionism, formalism and coherence dimensions.